Efektywność wykorzystania energii biogazu w gminach śląskich - Lorek, Elżbieta (The Efficiency of the Biogas Energy Utilization in the Silesian Administrative Districts, 2009)
In the article the current development perspectives of the renewable energy in European countries, particularly in Poland, are presented. Territorial systems of regaining the scrap energy in the light of the market development of modern energy technologies are discussed. The energetic and economic aspect of the biogas production coming from municipal wastes in the Silesian province is also presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 121-133